Innovations in radiotherapy for tongue squamous cell carcinoma - Songling Hu; Xiaofei Li; Bin Yang; Tian Yu; Fangyu Yi; Xiurong Qin; Cong Chen; Can Wang; Xin Yu; Jing Zhu (Journal of Translational Medicine)
Abstract Radiotherapy sensitivity is associated with the prognosis of patients with tongue squamous cell carcinoma (TSCC). In the present study, we proposed to explore the specific mechanism of interventional radiology (IR) therapy for TSCC in vitro and in vivo. TSCC cells were treated with 6 Gy IR and tumor bearing mice were treated with 20 Gy × 1 IR. DIA quantitative proteomics along with bioinformatics analysis were conducted in TSCC cells to investigate differential proteins related to IR and relation of which involved in TMEM147 and SPHK1 was confirmed by immunoprecipitation. Cell proliferation, apoptosis, autophagy& autophagy flux along with calcium signaling pathway detection were performed in vitro and in vivo. Our results showed that IR induced increasing calcium levels accompanied by up-regulated TMEM147 and down-regulated SPHK1 along with enhancing autophagy together with apoptosis. The effect of calcium overloading induced by IR on autophagy and apoptosis was dependent on increasing TMEM147 and decreasing SPHK1. However, IR-induced autophagy and apoptosis tended to be independent of only increasing calcium levels when down-regulating TMEM147 or up-regulating SPHK1 expression in vitro and in vivo. Our study suggested that calcium-mediated TMEM147/SPHK1 may promote autophagy and apoptosis to improve radiotherapy sensitivity in TSCC.